Students' Relational Thinking in Solving Word Problem Based Cognitive Style - Akhmad Syaiful Bahri; Agung Lukito; Masriyah Masriyah (SAINTIS Publishing, 2019)
This study is motivated by students' low relational thinking ability. Relational thinking is one of the interesting problems in mathematics education. In this study will be examined the ability of relational thinking field-dependent and independent students in solving the arithmetic word problem. The method used in this study is qualitative descriptive. This research was conducted on 7th-grade of junior school students of Surabaya. The subjects of this study were 1 student who had a field-independent cognitive style and 1 student who had a field-dependent cognitive style. The data of the students' relational thinking process is obtained through the results of solving arithmetic word problem and interviews. Subject selection is done using instrument group embedded figures test. The results of the research showed that students with cognitive field-dependent experiences had difficulties in thinking and have not been able to establish the relationship between information elements and previous knowledge to solve problems. Whereas students with independent field cognitive styles were capable of relational thinking, namely by building interrelationships between elements of information and prior knowledge and knowledge of the properties of structure to solve problems.